Niger's HIV Response : Targeted Investments for a Healthy Future - Fraser, Nicole (World Bank, Washington, DC, 2014)
The main objective of the study is to provide a comprehensive analysis of HIV and health financing needs, investment opportunities, and health system development in the context of the Government of Niger's HIV National Strategic Plan (NSP) 2013-17. The analysis provides support for HIV policy decision-making, investment scenarios and programmatic targeting and prioritization. In addition, the analysis helps Niger build the case for HIV and health impact investment including delivering estimates of health care savings as a result of these investments. The analysis was implemented by the World Bank in collaboration with UNAIDS from a request for analytical support from the Government of Niger. The study involved a desk review of HIV- and health-related evidence, epidemic trends and financial modeling. The Optima model (formerly Prevtool) was used to estimate optimal resource allocation during the NSP, and the impact and cost-effectiveness of past HIV investments. A financial commitment framework was used to estimate longer-term costs and savings of the HIV program and the fiscal dimension of HIV in Niger.